Qualified doctor and medical students' use of resources for accessing information: what is used and why?. (15th July 2014) - Brennan, Nicola; Edwards, Sarah; Kelly, Narcie; Miller, Alice; Harrower, Lucy; Mattick, Karen
Abstract Background Learning to access information using resources such as books and search engines is an important and fast changing challenge for doctors and medical students. Many resources exist to support evidence‐based clinical decision‐making, but a wide range of factors influences their use. Objective To explore qualified doctor and medical students' use of resources for accessing information and to determine what is used and why. Methods A stratified sample of 46 participants was recruited in Devon, UK. Participants kept a self‐report diary of resources used over a week. The diaries were then used to stimulate recall within a semi‐structured interview. Diary data were collated into tables of resource use. Qualitative data from the interviews were transcribed verbatim and thematically analysed. Results Many resources were used by participants but typically for a short duration of time. Categories of reasons for accessing resources were 'to check', 'to learn' and 'to demonstrate'. The two main factors influencing choice of information resource were 'ease of access' and 'quality of information'. Students accessed more information, for a longer duration. Discussion & Conclusion Resources must be quick to use, easy to access and tailored to the different purposes that they serve for qualified doctors and medical students.